(untitled) (Research, Society and Development, 2021)
Cosmetic products are essential items in everyday life and directly related to a good quality of life. This branch has been steadily growing in Brazilian market even in the midst of the economic crisis. Thence, it is the role of the Brazilian National Health Surveillance Agency (Anvisa) to establish standards, guidelines and surveillance actions in relation to these products. In this work, we therefore aimed to perform the descriptive analysis of cosmetics which were considered by Anvisa as irregular products between 2009 and 2020. Results were evaluated according to the following attributes: companies; motives; products; and inspection actions. The analysis encompassed a total of 872 notifications, which showcased that the majority of companies with irregular products are located in the Southeast region (64%), mainly in São Paulo. There was an expressive degree of recurrence of the notified companies, which together were responsible for 40% of the total withdrawals. The most frequent motivations for the application of sanctions were: the absence of product registration/notification (35.3%); quality deviations (25.9%); and the lack of a business license (20.0 %). The most commonly withdrawn products were those for hair use, which may indicate strong relation with the use in beauty salons. In addition, there was a large increase in the irregularity of antiseptic gels in 2020. The number of revocations was low, what suggests lack of adequate quality management in the notified companies. In conclusion, Anvisa has fulfilled its institutional objective of standardization, thereby establishing and enforcing adequate product safety countrywide.